Imaging Evaluation for Simulated RGBW Color LCDs With the Proposed Color Conversion Algorithm - Wang, Yen-Chin; Sheu, Chia-Rong (Journal of display technology, 2015)
This paper is a comparative evaluation of imaging performance for two types of color liquid crystal displays (LCDs) with Quad RGBW (red, green, blue, and white) and Stripe RGB (red, green, blue) pixel units by means of simulation study. In accordance with the study results, using the proposed color conversion algorithm could achieve color consistence and higher luminance for rendering images with RGBW rather than RGB pixel units. Simultaneously, instrumental color measurement via a spectrometer was done which results also proved that almost same color values of rendering images with RGBW pixel units as well as those images with original RGB pixel units, and higher luminance was achieved. Finally, the pseudocolor phenomenon of rendering images with RGBW pixel units is analyzed and discussed on the basis of human vision model.